Enhanced Zintl anions by carbon doping in Al‐Na clusters and new magic structure Al6Na4C. Issue 9 (6th December 2018) - Tang, Jianling; Zhang, Cairong; Du, Ning; Zhao, Yanyan; Chen, Hongshan
Abstract: This article investigated the low‐energy structures of Al6 Na m C ( m = 2, 4, 6, 8) clusters and their electronic structures by using genetic algorithm combined with density functional theory and configuration interaction methods. The computations show that the C atoms prefer sitting at the center, whereas the Na atoms tend to locate at the outside of the clusters. The valence molecular orbitals (MOs) agree well with the prediction of the jellium model. The stronger attraction of the central carbon to the valence electrons will depress the potential energies locally, which makes the 2S level go obviously lower and the 2P and 1D orbitals form a sub‐band. The 26 valence electrons in Al6 Na4 C form closed 1S 2 1P 6 2S 2 1D 10 2P 6 shells and correspond to a new magic structure. The MOs and electron localization function show that the sodium cores are exposed at the outside of the valence electrons and form naked cations. The contraction of the valence electrons because of the carbon doping enhances the charges on the Al6 C moieties, and the Na + cores on the peripheries are ionically bonded to the Zintl anions (Al6 C) q− . The Al6 Na4 C has a tetrahedral structure with symmetry Td, and it may be used as building blocks to synthesize Zintl solid. Abstract : The carbon atom doped in Al‐Na clusters depresses the potential locally and causes the 2S/2P orbitals to be considerably lower than that in pure metal clusters. The 26 valence electrons of Al6 CNa4 form closed 1S 2 1P 6 2S 2 2P 6 1D 10 shells and correspond to a new magic number with enhanced stability and large energy gap. The Al6 C forms a 4− anion and Al6 CNa4 is a potential building block for cluster assembled materials.